Mock-up experiment at Birmingham University for BNCT project of Osaka University – Neutron flux measurement with gold foil. (December 2015) - Tamaki, S.; Sakai, M.; Yoshihashi, S.; Manabe, M.; Zushi, N.; Murata, I.; Hoashi, E.; Kato, I.; Kuri, S.; Oshiro, S.; Nagasaki, M.; Horiike, H.
Abstract: Mock-up experiment for development of accelerator based neutron source for Osaka University BNCT project was carried out at Birmingham University, UK. In this paper, spatial distribution of neutron flux intensity was evaluated by foil activation method. Validity of the design code system was confirmed by comparing measured gold foil activities with calculations. As a result, it was found that the epi-thermal neutron beam was well collimated by our neutron moderator assembly. Also, the design accuracy was evaluated to have less than 20% error. Highlights: Accelerator based neutron source for BNCT is being developed in Osaka University. Mock-up experiment was carried out at Birmingham University, UK. Neutronics performance of our assembly was evaluated from gold foil activation. Gold foil activation was determined by using HPGe detectors. Validity of the neutronics design code system was confirmed.